A Bus-Service-Based Zone Division Approach for the Spatial Analysis of Public Bus: A Case Study in South China - Fanghao Fu; Jiemin Xie; Ming Cai; Wei Huang (Journal of Advanced Transportation)
Public bus is one of the major green transport modes in most cities, and a proper analysis of public bus can enhance its sustainable development. Hence, the analysis of public bus is always a hot research topic. Generally, to consider the heterogeneity in the studied area and reduce the computation difficulties, the study area is divided into multiple zones and then various analytical methods are applied. However, an improper zone division could lower the quality of the analysis results and then probably mislead the improvement strategy design. This study examines the influence of the two commonly used zone division methods (the grid-based method and the natural-boundary-based method) on the spatial analysis of public bus service using the analytical example. The result shows that the impact of zone division exists. Therefore, this study aims to identify the possible approach to reduce the negative impact and suggests a new zone division method, the bus-service-based (BS-based) method, for the spatial analysis of public bus service. The BS-based method is compared with the commonly used zone division methods using the real-world data, and the comparison results demonstrate that the BS-based method can be more efficient to support the spatial analysis of bus service.